2022
DOI: 10.3390/molecules27133979
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Phenolic Profile by Liquid Chromatography, Evaluation of Antioxidant Activity and Toxicity of Moroccan Erica multiflora, Erica scoparia, and Calluna vulgaris (Ericaceae)

Abstract: This study aimed to investigate the phenolic profile and selected biological activities of the leaf and aerial extracts of three Ericaceae species, namely Erica multiflora, Erica scoparia, and Calluna vulgaris, collected from three different places in the north of Morocco. The phenolic composition of all extracts was determined by LC coupled with photodiode array and mass spectrometry detection. Among the investigated extracts, that of E. scoparia aerial parts was the richest one, with a total amount of polyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…According to Amroun et al (2021) , flavonoid glycosides are the most abundant in this plant. On the other hand, Bekkai et al (2022) detected kaempferol-3- O -glucoside in three different E. arborea L. species. Identification of kaempferol 3- O -glucoside is also reported among thirty three flavonoid glycosides in the leaves of E. arborea L. in a previous report by Zengin et al (2019) , in which 72 different phenolic compounds were identified (21 phenolic acids, 27 flavonoid glycosides and 9 flavonoid aglycones, 6 flavan-3-ols, and proanthocyanidins).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to Amroun et al (2021) , flavonoid glycosides are the most abundant in this plant. On the other hand, Bekkai et al (2022) detected kaempferol-3- O -glucoside in three different E. arborea L. species. Identification of kaempferol 3- O -glucoside is also reported among thirty three flavonoid glycosides in the leaves of E. arborea L. in a previous report by Zengin et al (2019) , in which 72 different phenolic compounds were identified (21 phenolic acids, 27 flavonoid glycosides and 9 flavonoid aglycones, 6 flavan-3-ols, and proanthocyanidins).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, phenolic compounds found in EAME, possess significant analgesic activity, especially in prostaglandins pathway inhibitions ( Subedi et al, 2016 ). The biological activities of the extracts are closely related to their chemical composition ( Bekkai et al, 2022 ). In general, Kaempferol glycosides isolated from plants exert considerable anti-inflammatory and analgesic effects ( Khan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex nature of phytochemicals and their interactions, the importance of using various methods based on different mechanisms for a comprehensive study of the antioxidant properties of plant extracts has been argued (Bekkai et al, 2022). The effect of extracts at different concentrations was studied for their ability of hydrogen or electron transferring ability measured using DPPH and FRAPS tests.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the strong antioxidant activity of E. arborea extracts of different vegetal parts could be due to their richness on natural antioxidant substances (Luis et al, 201;Köroğlu et al, 2018). Shrubs of the family of Ericaceae are known as natural sources of bioactive compounds associated to their phenolic compounds composition (Bekkai et al, 2022;Köroğlu et al, 2018). The high phenolic content found in these species is thought to be linked to their strong free-radical scavenging effects and potential health related to therapeutic functions (Ay et al, 2007;Marquez-Garcia et al, 2009;Guendouze et al, 2015;Köroğlu et al 2018).…”
Section: Discussionmentioning
confidence: 99%